Pengaruh Manajemen Sumber Daya Manusia dan Motivasi Kepala Sekolah terhadap Disiplin Kerja Guru di Sekolah Islam Terpadu Kabupaten Tapanuli Tengah - Amrilsyah Butar-butar (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2021)
This study aims to verify the effect of human resource management and the motivation of school principals on the work discipline of teachers at SD IT Pandan in Central Tapanuli Regency. This research is a correlation research with a quantitative approach. The instrument used in this study was a questionnaire which was tested using validity and reliability tests, while the analytical technique used was quantitative analysis techniques. The results showed that there was a significant effect of human resource management on significant work discipline (Fcount (23.15) greater than Ftable (0.320)), there was also a significant influence of motivation on work discipline significantly (Fcount (38.04) greater than Ftable (0.320)). Meanwhile, based on multiple regression data analysis, the results showed that there was a significant influence of human resource management and motivation on the work discipline of teachers at SD IT Pandan in Central Tapanuli Regency. This is evidenced by the statistical results of multiple regression tests which show that Fcount (1.8) is greater than Ftable (0.320), then HO is rejected and Ha is accepted. In addition, the results obtained from the SPSS value which shows the value of Human Resource Management (β) 0.269 (**p0.05; p=0.000) and Giving Motivation (β) 0.303 (*p0.05; p=0.000) has a significant effect on the work discipline of teachers at SD IT Pandan in Central Tapanuli Regency. The contribution of the variable influence of human resource management and motivation to work discipline is (ΔR2) 0.144